RENTAL FEES FOR USING THE NON-RESIDENTIAL FUNDS OF THE MUNICIPAL FISC AND FACTORS OF ITS GROWTH - R. R. Yarullin (Russian Journal of Economics and Law)
Objective: to develop the theoretical bases of forming the rent fees for non-residential funds, which constitute the fisc of Ufa municipality, and to identify the opportunities of revenues increase from its use.Methods: abstract-logical, dialectical, comparative, systematic and structural, economic analysis and synthesis.Results: the content is disclosed of the rental fees of non-residential funds constituting the municipal fisc as a cash payment, of compensatory and equivalent character, for the use of the municipality fisc;the necessity is grounded of increasing the budget effectiveness of the municipal non-residential facilities rent, which consists in the proper use of rental fees for maintenance, investments in the renovation and construction of non-residential facilities, the availability of funds for their financing, and the lack of growth in rents above the economically viable threshold;186Экономика и управление народным хозяйствомEconomics and economic managementАктуальные проблемы экономики и права. 2015. № 4Actual Problems of Economics and Law. 2015. No. 4the factors are analyzed which determine the budget revenues from rent, affecting the fiscal efficiency of non-residential facilities rent in Ufa city;a number of problematic issues were identified, of systemic character: reduction of the number of rent contracts; reduction of the rented space;an excessive amount of the reduced rent; arrears of tenants on rents; insufficient quality of the information management system;ways are propose to improve the budget efficiency and profitability of the non-residential rent, consisting in the transition of non-residential buildings and premises, which are in economic conducting or in operational administration or are unused (unregistered), into the rent regime with the establish- ment of feasible rental fees; expanding the number of premises, the rental fee for the use of which is determined by bidding; reduction of benefits to commercial organizations for the rent payment; providing full and timely transfer of the arrears from tenants to the budget; acceleration of the formation of the automated system for mass valuation of real estate, allowing to automate the forecast of budget revenues from non-residential funds renting.Scientific novelty: the necessity is grounded to increase the budget effectiveness of the municipal non-residential facilities rent, the definition is formulated of the non-residential facilities rent of the municipal fisc and factors of its growth.Practical significance: the findings and conclusions of the article can be used in the budget efficiency management of the non-residential facilities rent, as well as in research and teaching activities.